Propagation of optical femtosecond pulses through quartz and glass ВК-7 - Leshchenko, V.P.; Povrozin, A.I.; Sotnikov, G.V.; Vasiliev, A.V.; Galaydych, K.V.; Karelin, S.Yu. (Вопросы атомной науки и техники, 2019)
In the approximation of dispersion theory to the fourth order inclusive, a theoretical study of the propagation of optical femtosecond pulses of a Gaussian profile and a profile proportional to the hyperbolic secant through quartz and BK-7 glass was carried out. Based on the solutions of the equations for the propagation of pulses of various initial durations through optical materials, dependencies "material length − pulse duration" are obtained. It is shown that, compared with the second approximation of dispersion theory, the fourth approximation gives a slightly lengthy pulse duration. Peculiarities of various time pulse profiles on the pulses duration are also shown. Analytical consideration is confirmed by numerical calculations. Теоретично досліджено проходження оптичних фемтосекундних iмпульсiв гаусового профіля та профіля, пропорцiйного гiперболiчному секансу, через кварц та скло ВК-7 у наближеннi теорії дисперсiї до четвертого порядка включно. На основі рішень рівнянь проходження iмпульсiв рiзної початкової тривалостi через оптичнi матерiали побудовано графiки залежностей «довжина матерiалу – тривалість імпульсу». Показано, що в порівнянні з другим наближенням теорії дисперсії четверте наближення незначно впливає на залежність тривалості імпульсів від довжини оптичного матеріалу. Також показано особливості впливу дисперсії оптичних материіалів на тривалість імпульсів різних часових профілей. Аналітичний розгляд підтверджено чисельними розрахунками. Теоретически исследовано прохождение оптических фемтосекундных импульсов гауссового профиля и профиля, пропорционального гиперболическому секансу, через кварц и стекло ВК-7 в приближении теории дисперсии до четвёртого порядка включительно. На основании решений уравнений прохождения импульсов различной начальной длительности через оптические материалы построены графики зависимостей «длина материала – длительность импульса». Показано, что по сравнению со вторым приближением теории дисперсии четвёртое приближение незначительно влияет на зависимость длительности импульсов от длины оптического материала. Также показаны особенности влияния дисперсии оптических материалов на длительность импульсов различных временных профилей. Аналитическое рассмотрение подтверждено численными расчётами.